2020
DOI: 10.1177/1362361320922658
|View full text |Cite
|
Sign up to set email alerts
|

Examining the relationship between parent physical activity support behaviour and physical activity among children and youth with autism spectrum disorder

Abstract: Children and youth with autism spectrum disorder engage in less physical activity than neurotypically developing peers. This may be due to factors associated with autism spectrum disorder at the individual and environmental level that can make physical activity participation more challenging. Parent support is a known determinant of physical activity among children and youth; however, limited research has explored the relationship between parent physical activity support behaviour and child physical activity b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…PA messages targeting people with disabilities tend to lack theory-based content [ 66 ] and it is recommended that PA messages targeting parents of CWD include content regarding theoretical predictors of behaviour change to further enhance message effectiveness [ 11 ]. For example, there may be value in developing messages that target the important predictors of parent support for PA among parents of CWD such as perceived behavioural control, subjective norms, attitudes toward parent support for PA, motivation, behavioural regulation and planning [ 67 , 68 , 69 , 70 ]. Parents of CWD have specifically expressed a desire for messages regarding tools and strategies to support their own planning and self-regulatory behaviours [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…PA messages targeting people with disabilities tend to lack theory-based content [ 66 ] and it is recommended that PA messages targeting parents of CWD include content regarding theoretical predictors of behaviour change to further enhance message effectiveness [ 11 ]. For example, there may be value in developing messages that target the important predictors of parent support for PA among parents of CWD such as perceived behavioural control, subjective norms, attitudes toward parent support for PA, motivation, behavioural regulation and planning [ 67 , 68 , 69 , 70 ]. Parents of CWD have specifically expressed a desire for messages regarding tools and strategies to support their own planning and self-regulatory behaviours [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Caregivers can provide important social support needed to facilitate more physical activity among people with ASD. Indeed, recent research has demonstrated that supportive others “play an instrumental role in the physical activity behaviour of children and youth with autism spectrum disorder” (Brown et al, 2020). For their part, sport and recreation managers can take steps to promote physical activity for all populations.…”
Section: Discussionmentioning
confidence: 99%
“…Communicating the benefits of and opportunities to be physically active could serve to promote more physical activity among people with ASD (Sorensen & Zarrett, 2014). Parents and caregivers play an important role, especially when considering the time they spend with people with ASD (Brown et al, 2020). These individuals might communicate encouragement or provide the instruction needed to maintain a physically active lifestyle.…”
Section: Introductionmentioning
confidence: 99%
“…The association between such parental support and observed levels of PA in children has been documented by Seibert et al (2016) who found that parent support and a parent's perceptions of his/her child's physical abilities predicted PA in children with disabilities. Similarly, Brown et al (2020) found that among parents of school-age children with ASD, parent intentions to support PA were associated with parent PA support behaviors, which in turn predicted PA in children. Their research illustrates the important role parents play in promoting PA among children with NDs.…”
Section: Introductionmentioning
confidence: 90%
“…While PA is not the sole predictor of healthy weight in children, it is considered a protective factor against the risk for overweight and is also a modifiable factor that could be addressed in many settings. Given the important role parents play in promoting PA (e.g., Brown et al, 2020), in this study, we explore the association between parental beliefs in the value of PA and weight status in children with NDs. In doing so, we estimate the degree to which differences in parental beliefs about the benefits of PA predict differences in the proportions of children with NDs classified as overweight and obese, whilst also considering as potential confounders other social and environmental factors that have been associated with body composition (and health disparities) in prior research (e.g., child race and ethnicity, household income, cognitive functioning, adaptive behavior, and sleep patterns).…”
Section: Introductionmentioning
confidence: 99%